Comparison Clinical Outcomes of Sepsis Caused by Multidrug-Resistant (MDR) and Non-MDR Klebsiella pneumoniae - Fadrian, Fadrian; Ahmad, Armen; Linosefa, Linosefa; Simanjuntak, Rohayat Bilmahdi; Putri, Vidola Yasena (Faculty of Medicine, Universitas Diponegoro, 2026)
Background: Klebsiella pneumoniae is a common pathogen causing sepsis and is associated with high morbidity and mortality. The emergence of multidrug-resistant organisms (MDROs), particularly extended-spectrum β-lactamase-producing K. pneumoniae (ESBL-KP) and carbapenem-resistant K. pneumoniae (CRKP), has limited antimicrobial therapy options and may worsen clinical outcomes such as mortality and length of hospital stay (LOS). Objective: This study aims to compare the clinical characteristics and outcomes of sepsis caused by multidrug-resistant K. pneumoniae and non-resistant strains, focusing on mortality and LOS.Methods: An observational analytical study with a cohort design was conducted at Dr. M. Djamil General Hospital in Padang from October 2024 to January 2025. Subjects diagnosed with sepsis due to pneumonia and confirmed positive for K. pneumoniae through blood or respiratory cultures were included using consecutive sampling. Isolates were categorized into MDR (ESBL-KP and CRKP) and non-MDR. Clinical data were analyzed descriptively to described subject characteristics, while bivariate analysis (chi-square and independent t-test) evaluated associations between resistance profiles and outcomes, focusing on mortality and LOS (p < 0.05). Results: Of the 70 subjects, 39 (55.7%) had confirmed infection with MDR strains and 31 (44.3%) with non-MDR.Mortality was highest in the CRKP (56.5%), followed by non-MDR (38.7%) and ESBL-KP (25.0%). Statistical analysis revealed a notable association between the resistance profiles of K. pneumoniae and mortality (p < 0.001 for both CRKP and ESBL-KP vs non-MDR). However, there were no statistically significant differences in mean hospital LOS across the groups (CRKP: 16.30 ± 9.81 days; ESBL-KP: 13.63 ± 9.77 days; non-MDR: 16.06 ± 9.49 days; all p > 0.05). Conclusion: Sepsis caused by multidrug-resistant K. pneumoniae, including both ESBL and CRKP, is significantly associated with increased mortality. Early identification and appropriate antimicrobial management are essential to improve subject outcomes.